Nitrogen, Phosphorus, Mowing Height, and Arbuscular Mycorrhiza Effects on Red Fescue and Mixed Fescue–Bentgrass Putting Greens. Issue 2 (26th October 2016) - Calvache, Sara; Espevig, Tatsiana; Andersen, Tina E.; Joner, Erik J.; Kvalbein, Agnar; Pettersen, Trond; Aamlid, Trygve S.
Abstract : Red fescue (RF, Festuca rubra L.) is used on golf putting greens in the Nordic region due to its high disease resistance and low requirements for nitrogen (N) and water, but low density and growth rate makes RF susceptible to annual bluegrass (AB, Poa annua L.) invasion. Putting greens seeded with RF + bentgrass ( Agrostis sp.) may be more competitive with AB but also have different playing characteristics. Our objective was to compare RF, RF + colonial bentgrass (CB, Agrostis capillaris L.), and RF + velvet bentgrass (VB, Agrostis canina L.) putting greens at two mowing heights (4.0 or 5.5 mm), three N rates (5, 10, or 15 g N m −2 yr −1 ), and three phosphorus (P)–arbuscular mycorrhizal fungi treatments (0 and 1.8 g P m −2 yr −1 without inoculation and 0 g P m −2 yr −1 with inoculation). The four‐factorial experiment was conducted in 2011 and 2012 at Landvik, Norway. Red fescue provided lower visual quality and density and less competition against AB than RF + bentgrass combinations. Increasing the N rate from 5 to 15 g N m −2 yr −1 increased the proportion of bentgrass tillers from 53 to 64% in RF + CB and from 86 to 92% in RF + VB. Surface hardness increased in the order RF + VB < RF + CB < RF turfs. Ball‐roll distance decreased with increasing N rate and was longer with RF and RF + VB than with RF + CB. The main effects of N and mowing height on AB invasion were not significant, but lower mowing increased AB competition in RF. Mycorrhiza colonization of roots was not significantly affected by any practice, and neither P nor arbuscular mycorrhizal fungi influenced the competition against AB.